The Crisis of Physical Education in the Discourse of Mimicry: Ukrainian and Global Contexts - Sainchuk Mykola; Petrachkov Oleksandr; Sainchuk Anna; Verbyn Nazarii (Sciendo, 2022)
This study presents a qualitative analytical approach through a critical analysis of data to critically describe, interpret, and explain the crisis in physical education (PE) in Ukraine and the world. The subject of consideration is the Ukrainian PE curriculum, which must be followed by all teachers when making lesson plans. Among the many different obstacles for Ukrainian PE, the study focused on one of the most important and hidden barriers, which is a kind of multiplier of the crisis - the culture of mimicry. Institutional mimicry is a serious problem that has been poorly analyzed, but it is actually very significant and often causes crises or slows down the progress of PE. Ignoring or failing to understand the factor of mimicry reduces the possibility of escaping a crisis or even makes escape impossible. The results show that the mimicry of PE is at least two-tiered: on the one hand, it is bureaucratic (external), and on the other, it is "internal" (based on tradition). Mimicry in the Ukrainian reality of PE is not advertised, but there is almost no alternative path for development. The constant mimicry of PE in Ukraine has created a paradoxical situation in which scientific expediency yields to politics and eventually leads to a new crisis. The study shows that there is a missing culture of influence on political decisions in Ukraine. Ukrainian PE teachers have a culture of mimicry, not a culture of leadership. The Ukrainian PE curriculum for secondary schools contains contradictions in its theoretical and practical parts.